PENINGKATAN KETERAMPILAN GURU MEMANFAATKAN MEDIA IT DALAM PEMBELAJARAN MELALUI WORKSHOP TPOEG - Wahyu Purwanto (LPMP Provinsi DKI Jakarta, 2022)
The Workshop of Guidance and training through The Power of Edu Game (TPOEG) aims to improve the teacher’s skill of using IT media at SMP Negeri 1 Lumajang. This research uses school action research method. The instruments of this research are observation sheets, documentation, and interviews. The results showed that the implementation of the TPOEG workshop could improve the skills of teachers in the use of IT media in the first cycle by 80.33% to 90.56%. This is also supported by data on the level of student happiness (well-being student) after participating in edu games with an average student response of 90.36% or very good. Based on these results, the integration of edu games is proven to make learning fun for students, therefore teachers can recommend them in further learning. Further development related to the integration of edu games in learning can be done through the group of School Subject Teacher Consultation (MGMPS).